2021
DOI: 10.1038/s41598-021-93346-x
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the genetic link between type 1 and type 2 diabetes using functional genomics

Abstract: There is evidence pointing towards shared etiological features between type 1 diabetes (T1D) and type 2 diabetes (T2D) despite both phenotypes being considered genetically distinct. However, the existence of shared genetic features for T1D and T2D remains complex and poorly defined. To better understand the link between T1D and T2D, we employed an integrated functional genomics approach involving extensive chromatin interaction data (Hi-C) and expression quantitative trait loci (eQTL) data to characterize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…In addition to the rs7903146, we also identified SNP rs34855922 associated to T2D similar with (24), which again demonstrates the effectiveness of BayesR model combined with CSs. The rs7903146 and rs34855922 are two of the eight SNPs that mark regulatory elements within TCF7L2 locus (33). The rs7903146 coordinate regulation of TCF7L2 expression, and overlaps histone modification marks and an annotated enhancer in the pancreas (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the rs7903146, we also identified SNP rs34855922 associated to T2D similar with (24), which again demonstrates the effectiveness of BayesR model combined with CSs. The rs7903146 and rs34855922 are two of the eight SNPs that mark regulatory elements within TCF7L2 locus (33). The rs7903146 coordinate regulation of TCF7L2 expression, and overlaps histone modification marks and an annotated enhancer in the pancreas (33).…”
Section: Discussionmentioning
confidence: 99%
“…The rs7903146 and rs34855922 are two of the eight SNPs that mark regulatory elements within TCF7L2 locus (33). The rs7903146 coordinate regulation of TCF7L2 expression, and overlaps histone modification marks and an annotated enhancer in the pancreas (33). Our study also identified an intronic variant (rs145034729) at the TCF7L2 locus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T1D and T2D disproportionally affect adults and youth, respectively, with T2D being more common in adults. However, it has been identified that ~15% of common genes between T1D and T2D encode for proteins targeted by FDA-approved drugs [53,54]. Some of those drugs cause diabetes or diabetes-like symptoms themselves, including hypoglycemia (i.e., streptozotocin, pembrolizumab, nivolumab, and doxorubicin).…”
Section: Treatment Of Diabetesmentioning
confidence: 99%
“…To this end, efforts have been made to develop analytical pipelines that integrate genetic, genomic and biological data to produce networks that indicate connectivity between GWAS loci and candidate causal genes. For example, Nyaga et al ( Nyaga et al, 2021 ) used integrated genomics to ask whether there were any shared genetic features of type I diabetes (T1D) and T2D; their functional approach integrated Hi-C and eQTL data to characterise the functional impacts of disease-associated SNPs, identifying genetic regulatory regions that alter regulation of genes common to both T1D and T2D, that are associated with disease development. Additionally, Fernández-Tajes et al ( Fernández-Tajes et al, 2019 ) present an analytical pipeline to define the transcriptional activity of T2D-associated SNPs, integrating genomic data to reveal connectivity between candidate genes at T2D GWAS loci.…”
Section: Introductionmentioning
confidence: 99%